Continuation load flow method parameterized by transmission line power losses - Alves, D. A. [UNESP]; De Silva, L. C.P.; Castro, C. A.; Da Costa, V. F. (Institute of Electrical and Electronics Engineers (IEEE), 2000)
The conventional load flow methods are considered to be inadequate to obtain the maximum loading point (MLP) due to ill-conditioning problems at and near this critical point. As far as the Newton method is concerned, the Jacobian matrix becomes singular at MLP. Continuation methods are efficient tools for solving this kind of problem, since different parameterizations are used in order to avoid such ill-conditioning problems. In this paper new parameters are presented and tested, namely the transmission line power losses (real and reactive). The results obtained with the new approach for the IEEE test systems (14, 30, 57 and 118 buses) show that the characteristics of the conventional method are enhanced and it is possible to obtain operating points beyond the singular solution. Several tests were also carried out to compare the performance of different parameterization schemes for the continuation load flow method by the use of secant and tangent predictors.
Keywords: continuation methods; load flow; maximum loading point; Voltage stability